2005
DOI: 10.1177/147323000503300207
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine Treatment on Oxidative Stress in Acetic Acid-induced Experimental Colitis in Rats

Abstract: We assessed the possible protective effects of N-acetylcysteine (NAC) against toxic damage in the rat colon. Two doses of NAC (20 mg/kg and 100 mg/kg) given for 2 days and 7 days after acetic acid administration (to induce colitis) were tested. NAC was dissolved in saline and administered locally (intracolonic), systemically (intraperitoneal) or in a combination (intracolonic and intraperitoneal). Several parameters, including macroscopic and histopathological scores and myeloperoxidase, glutathione and nitric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 21 publications
4
39
1
1
Order By: Relevance
“…When considering that the use of substances with antioxidant activity can neutralize the harmful effects of OFRs, it becomes an interesting strategy for the treatment of diseases related to oxidative stress. Studies conducted in experimental models of chemically induced colitis confirmed the beneficial effects of antioxidants, improving the inflammatory process of colonic mucosa [27][28][29][30][31] . Several drugs have been tested with effective results in experimental conditions, including 5-ASA, glucocorticoids, L-carnitine, L-glutamine, melatonin and antioxidants found in the aqueous extract of Ilex paraguariensis and Curcuma longa [33][34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…When considering that the use of substances with antioxidant activity can neutralize the harmful effects of OFRs, it becomes an interesting strategy for the treatment of diseases related to oxidative stress. Studies conducted in experimental models of chemically induced colitis confirmed the beneficial effects of antioxidants, improving the inflammatory process of colonic mucosa [27][28][29][30][31] . Several drugs have been tested with effective results in experimental conditions, including 5-ASA, glucocorticoids, L-carnitine, L-glutamine, melatonin and antioxidants found in the aqueous extract of Ilex paraguariensis and Curcuma longa [33][34][35][36][37][38][39] .…”
Section: Discussionmentioning
confidence: 83%
“…It is filterable and easily crosses the cellular membranes, with easy access to different intracellular compartments 29 . NAC has been used as an antioxidant both in vivo and in vitro, in different situations 29,30 and it has been used in clinical practice to treat several diseases, including pulmonary disorders caused by excess oxygen, against the paracetamol toxic effects, infection of human immunodeficiency virus, and the treatment of disorders caused by ischemia in liver, lungs and skin flaps 37,40,41 . The possibility of different pharmacological applications is regulated by the chemical properties of the group of thiol-cysteine molecules to eliminate OFRs 30 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations